Analisis Pengendalian Kualitas AMDK Cup 220 ML Menggunakan Metode Six Sigma Di PT. Taubah Jaya Abadi Berau, Kalimantan Timur - Hasto Wisnugroho, Anthonius Dhinar; Andriani, Maria Kiki (Jurnal Inkofar, 2023)
PT. Taubah Jaya Abadi is a company who production of Bottled Drinking Water (AMDK) with the Destine brand, producing 220 ml cups, 250 ml and 600 ml bottles, and 19 liter gallons. The highest problems occurred in 220 ml cup packaging products, namely reduced product volume, dented cups, slanted lids, leaky lids, and trimming. Purpose of this study was to determine the level of DPMO defects and sigma values for the factors that cause product defects. Method used six sigma with the Define, Measure, Analyze, Improve and Control (DMAIC) stages. Results showed that the causes of product defects came from 5 causes of human factors, 9 causes of machine factors, 5 causes of method factors, 6 causes of material factors, and 1 causes of environmental factors. Proposed improvements using the FMEA method, inspection of of raw materials sample and operator training on operating process the equipment and workings.